Chylolymphatic Cyst - Presenting as Acute Intestinal Obstruction – A Case Report - Arora, Sunita; Kaur, Taranjeet; Singh Rana, Harwinder (Journal of Nepal Paediatric Society, 2022)
Chylolymphatic cyst is one of the rare variants of mesenteric cysts. These cysts are present within mesentery and contain chylous or lymphatic fluid. Chylolymphatic cysts are rare in paediatric age group. We present a case of a four years old boy who presented with features of acute intestinal obstruction. CECT abdomen revealed a hypodense cystic mass in the peritoneal cavity. Exploratory laparotomy of the abdomen revealed a solitary cyst measuring 10.7 cm x 9.4 cm x 10.5 cm which was adherent to the loops of small intestine and right kidney. Complete excision of cyst along with resection of the adjacent gut and end to end anastomosis was done. Histopathology of the excised cyst was suggestive of chylolymphatic cyst. It has been highlighted that chylolymphatic cyst can be a rare cause of intestinal obstruction in children.